Terebellidae (Polychaeta) from Coiba National Park, Panamanian Pacific, including description of four new species and synonymy of the genus Paraeupolymnia with Lanicola - Capa, María; Hutchings, Pat A. (Zootaxa, 2006)
Four new species of terebellids (Terebellidae, Polychaeta) associated with hard substrates in the Coiba National Park (Panamanian Pacific) are described. The diagnostic features of each species within their respective genera are as follows: Eupolymnia joaoi sp. nov. has an enlarged second pair of lateral lobes, nephridial papillae present on segments 3–8, 14 ventral pads, neuropodial tori with uncini arranged in one single row in segments 5–10, and uncini with two rows of 2–3 teeth each over the main fang; Lanicola guillermoi sp. nov. has prostomial eyespots and a characteristic shape and dental formula of the uncini, with a larger tooth on the first row over the main fang and 3–5 teeth on the second row; Lanicola eduardoi sp. nov. lacks prostomial eyespots and has a characteristic uncinial dental formula on anterior and posterior segments of MF:3:2 and MF:1:1–3, respectively; Thelepus fraggleorum sp. nov. has branchial filaments separated by a wide dorsal gap, a characteristic uncinial dental formula of MF:2:1 on anterior uncini and MF:2–3:1–3 on posterior, and notopodia on more than half of anterior segments. In addition, the status of Terebella gorgonae and Eupolymnia regnans, two species previously recorded from the Panamic Province (Tropical Eastern Pacific), is examined. Descriptions of the syntype of E. regnans and of possible specimens of “Terebella” cf. Terebella gorgonae from the Coiba National Park are provided. The genus Paraeupolymnia is synonymised with Lanicola, and the diagnosis of Lanicola is emended.